Cognitive Function Training System Using Game-Based Design for Elderly Drivers. Issue 19 (2016) - Hiraoka, Toshihiro; Wang, Ting-Wen; Kawakami, Hiroshi
Abstract: It has been found that age-related decline of cognitive ability is one of risk factors for traﬃc accidents among the elderly. Therefore, the present study introduced a new game- based cognitive function training system, which was designed by cognitive evaluation theory, gamiﬁcation, interface design guidelines for driver-assistance systems and fuben-eki principle. It uses a trail making game to train and measure driver's visual attention ability, and the score was transformed to limit the vehicle's maximum velocity. Simulator experiments were performed to verify that it enlarged the degree of useful ﬁeld of view to enhance the hazard perception ability.